2017
DOI: 10.3389/fmicb.2017.00034
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages and Bacterial Plant Diseases

Abstract: Losses in crop yields due to disease need to be reduced in order to meet increasing global food demands associated with growth in the human population. There is a well-recognized need to develop new environmentally friendly control strategies to combat bacterial crop disease. Current control measures involving the use of traditional chemicals or antibiotics are losing their efficacy due to the natural development of bacterial resistance to these agents. In addition, there is an increasing awareness that their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
330
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(336 citation statements)
references
References 152 publications
(167 reference statements)
1
330
0
5
Order By: Relevance
“…Bacteriophages and phage-derived proteins have recently been employed against several plant pathogens (15,16). Lytic phages contain a large reservoir of genes specifically involved in killing their host cells and are attractive as biocontrol agents.…”
mentioning
confidence: 99%
“…Bacteriophages and phage-derived proteins have recently been employed against several plant pathogens (15,16). Lytic phages contain a large reservoir of genes specifically involved in killing their host cells and are attractive as biocontrol agents.…”
mentioning
confidence: 99%
“…Бактериофаги являются наиболее рас-пространенным биологическим объектом в био-сфере, представительство которых составляет 10 31 организмов, в то время как общее число прокари-отических клеток в биосфере составляет около 10 30 [7]. Бактериофаги находятся в любой среде, в ко-торой присутствуют бактерии.…”
Section: Introductionunclassified
“…Порядок Caudovirales состоит из трех фаговых семейств: Myoviridae -с жесткими сократительны-ми хвостами, Podoviridae -с короткими, не сокра-щающимися хвостами и Siphoviridae -с длинными гибкими хвостами. Фаги, принадлежащие к другим семействам, имеют изменчивую морфологию с ге-номами различного состава нуклеиновых кислот [7]. Бактериофаги, вызывающие гибель бактерий, не индуцируют развитие резистентности бактерий к противомикробным препаратам, недорогие в про-изводстве и безопасны для людей [8] В зависимости от вида высвобождения новых вирионов из бактерий бактериофаги делят на ли-тические и лизогенные.…”
unclassified
“…Soon after the discovery of bacteriophages by d’Herelle and Twort at the beginning of the 20 th century [1,2], the potential to use these bacterial viruses as a therapeutic was recognized. Although the first applications of phages focused on human medicine [3], other fields including agriculture soon began to explore the potential of bacteriophages as biocontrol agents [4]. The first isolation of phages infecting plant pathogenic bacteria (PPB) dates back to 1924, when it was shown that Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%